Reactivity of Anodically Generated 4-Methoxystilbene Cation Radicals: The Influence of Ortho-Substituted Hydroxymethyl, Aminomethyl, and Carboxylic Acid Groups - Chong, Kam Weng; Thomas, Noel Francis; Low, Yun Yee; Kam, Toh Seok (American Chemical Society, 2018)
The effect of ortho′-substituted side chains bearing nucleophilic groups such as CH 2 OH, CH 2 NHR, and CO 2 H on the reactivity of anodically generated 4-methoxy- and 3,4-dimethoxystilbene cation radicals was investigated, and results were compared with those of substrates where the nucleophilic groups such as OH and NHR are directly attached to the aromatic ring. It was found that when ortho′-substituted groups such as CH 2 OH or CH 2 NHR are present in the other ring, only direct intramolecular cation-nucleophile reactions occur to give bisbenzopyrans or bisisoquinolines. Crossover products (previously obtained when the ortho′ substituents were OH and NH 2 ) such as the fused benzoxepanes/fused benzoazepanes were not formed. When the ortho′ substituent is COOH, direct intramolecular cation-nucleophile reaction occurs to give the corresponding bis-δ-lactones in high yield. The presence of an additional 3-methoxy substituent resulted in the formation of other fused polycyclic products due to competing aromatic substitution reactions. Reaction pathways leading to the different products and reasons for the difference in behavior shown by the present stilbenes are presented. The results have provided additional insight into the reactivity and behavior of anodically generated stilbene cation radicals.